On being internally the same - Parrott, M; Gomes, AD (Oxford University Press, 2021)
Internalism and externalism disagree about whether agents who are internally the same can differ in their mental states. But what is it for two agents to be internally the same? Standard formulations take agents to be internally the same in virtue of some metaphysical fact, for example, that they share intrinsic physical properties. Our aim in this chapter is to argue that such formulations should be rejected. We provide the outlines of an alternative formulation on which agents are internally the same in virtue of facts about their epistemic capacities. The resulting formulation is one on which internalism and externalism are views about the extent to which an agent’s mental states can vary independently of the capacity for introspective discrimination. We suggest that this epistemic formulation of internalism and externalism picks out a substantive disagreement in philosophical theorizing about the nature of the mind.